Influence of gestational diabetes on fetal autonomic nervous system: a study using phase‐rectified signal‐averaging analysis. (26th July 2018) - Lobmaier, S. M.; Ortiz, J. U.; Sewald, M.; Müller, A.; Schmidt, G.; Haller, B.; Oberhoffer, R.; Schneider, K. T. M.; Giussani, D. A.; Wacker‐Gussmann, A.
ABSTRACT: Objectives: Maternal gestational diabetes mellitus (GDM) is known to influence fetal physiology. Phase‐rectified signal averaging (PRSA) is an innovative signal‐processing technique that can be used to investigate fetal heart signals. The PRSA‐calculated variables average acceleration capacity (AAC) and average deceleration capacity (ADC) are established indices of autonomic nervous system (ANS) function. The aim of this study was to evaluate the influence of GDM on the fetal cardiovascular and ANS function in human pregnancy using PRSA. Methods: This was a prospective clinical case–control study of 58 mothers with diagnosed GDM and 58 gestational‐age matched healthy controls in the third trimester of pregnancy. Fetal cardiotocography (CTG) recordings were performed in all cases at entry to the study, and a follow‐up recording was performed in 19 GDM cases close to delivery. The AAC and ADC indices were calculated by the PRSA method and fetal heart rate short‐term variation (STV) by CTG software according to Dawes–Redman criteria. Results: Mean gestational age of both groups at study entry was 35.7 weeks. There was a significant difference in mean AAC (1.97 ± 0.33 bpm vs 2.42 ± 0.57 bpm; P < 0.001) and ADC (1.94 ± 0.32 bpm vs 2.28 ± 0.46 bpm; P < 0.001) between controls and fetuses of diabetic mothers. This difference could not be demonstrated using standard computerized fetal CTG analysis of STV (controls, 10.8 ± 3.0 ms vs GDM group, 11.3 ± 2.5 ms; P = 0.32). Longitudinal fetal heart rate measurements in a subgroup of women with diabetes were not significantly different from those at study entry. Conclusions: Our findings show increased ANS activity in fetuses of diabetic mothers in late gestation. Analysis of human fetal cardiovascular and ANS function by PRSA may offer improved surveillance over conventional techniques linking GDM pregnancy to future cardiovascular dysfunction in the offspring. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.